Easter communion in Polish synodal legislation of XIII-XVIII centuries - GRĘŹLIKOWSKI, JANUSZ (Prawo Kanoniczne, 2014)
Polish synodal legislation in period before Polish partition (XIII-XVIII century) devoted a lot of place and attention to the sacrament of the Eucharist. Church religious idea and Polish bishop’ legislation thought of that period explained the mystery of the Eucharist, defended it against mistakes and misunderstanding, specified legal standards for its performance, storage, giving and taking. It also referred to the duty of taking the Holy Communion in Easter time, which is interesting element of religion and cultic life of the Church in Poland. Taking the Eucharist at least once a year was to certain degree a touchstone and reflection of contemporary religious life of the faithful, it showed experiencing and understanding of faith’s truths as well as stimulated for living in accordance with the faith and commandments. Therefore it had impact on the whole of religious life. Polish synodal legislation regulating the issue of Easter Communion indicated how much the synodal legislators took care of supernatural life of the faithful, were the Eucharist was to create the source and strength of religious life. Undertaking the legislation action on the synods, they were aware that without the Eucharist there is no Church and religious life, as well as by created legal regulations they had an impact so the faithful, by taking the Holy Communion, realized vocation for the holiness and salvation. Annual Holy Communion taken in Easter period should guarantee that to some extent, providing certain minimum that the faithful supposed to maintain. Stipulations included in presented Polish synodal resolutions in XIII-XVIII century regarding the Easter Communion had significant impact on religious life in Poland, including the correct understanding and approach to the Eucharist, cult and Eucharistic life of the priesthood and secular faithful. Synods’ statutes composed the valid code of Polish church law, though. From there people took such information and knowledge, as what the Eucharist is, what its meaning for the life and conduct of each Christian is, when and how one should take it with dignity and fruitful effects, as well as what is a minimum of its taking. It can be said that synodal legislation in Poland before partitions provided effective remedy to the needs of Polish Church and religious life of the faithful. Whereas synodal legislators created and built the foundations and roots for our faith, principles of Christian life, including the Eucharistic one.